Learning from the Germans : race and the memory of evil - Neiman, Susan (Farrar, Straus and Giroux, 2019)
"As an increasingly polarized America fights over the legacy of racism, Susan Neiman, author of the contemporary philosophical classic Evil in Modern Thought, asks what we can learn from the Germans about confronting the evils of the past."--Provided by publisher.